The Peroxymonocarbonate Anion HCO4− as an Effective Oxidant in the Gas Phase: A Mass Spectrometric and Theoretical Study on the Reaction with SO2 - Chiara Salvitti; Federico Pepi; Anna Troiani; Marzio Rosi; Giulia de Petris (Molecules, 2022)
The peroxymonocarbonate anion, HCO4−, the covalent adduct between the carbon dioxide and hydrogen peroxide anion, effectively reacts with SO2 in the gas phase following three oxidative routes. Mass spectrometric and electronic structure calculations show that sulphur dioxide is oxidised through a common intermediate to the hydrogen sulphate anion, sulphur trioxide, and sulphur trioxide anion as primary products through formal HO2−, oxygen atom, and oxygen ion transfers. The hydrogen sulphite anion is also formed as a secondary product from the oxygen atom transfer path. The uncommon nucleophilic behaviour of HCO4− is disclosed by the Lewis acidic properties of SO2, an amphiphilic molecule that forms intermediates with characteristic and diagnostic geometries with peroxymonocarbonate.